Bacterial phytochrome as a scaffold for engineering of receptor tyrosine kinases controlled with near-infrared light - Leopold, Anna V. (J Mol Biol, 2020)
Optically controlled receptor tyrosine kinases (opto-RTKs) allow regulation of RTK signaling using light. Until recently, the majority of opto-RTKs were activated with blue-green light. Fusing a photosensory core module of Deinococcus radiodurans bacterial phytochrome (DrBphP-PCM) to the kinase domains of neurotrophin receptors resulted in opto-RTKs controlled with light above 650 nm. To expand this engineering approach to RTKs of other families, here we combined the DrBpP-PCM with the cytoplasmic domains of EGFR and FGFR1. The resultant Dr-EGFR and Dr-FGFR1 opto-RTKs are rapidly activated with near-infrared and inactivated with far-red light. The opto-RTKs efficiently trigger ERK1/2, PI3K/Akt and PLC-gamma signaling. Absence of spectral crosstalk between the opto-RTKs and GFP-based biosensors enable simultaneous Dr-FGFR1 activation and detection of calcium transients. Action mechanism of the DrBphP-PCM-based opto-RTKs is considered using the available RTK structures. DrBphP-PCM represents a versatile scaffold for engineering of opto-RTKs that are reversibly regulated with far-red and near-infrared light.